Serum Ratio of Free Triiodothyronine to Thyroid-Stimulating Hormone: A Novel Index for Distinguishing Graves’ Disease From Autoimmune Thyroiditis - Wu, Zhiyong; Zhu, Yu; Zhang, Min; Wang, Chen; Zhou, Lingli; Liu, Wei; Yang, Wenjia; Li, Meng; Zhang, Simin; Ren, Qian; Han, Xueyao; Ji, Linong (Frontiers in Endocrinology, 2021)
Objective Graves’ disease (GD) and autoimmune thyroiditis (AIT) are two major causes of thyrotoxicosis that require correct diagnosis to plan appropriate treatment. The objectives of this study were to evaluate the usefulness of thyroid-related parameters for distinguishing GD from AIT and identify a novel index for differential diagnosis of thyrotoxicosis. Design This retrospective study was performed using electronic medical records in Peking University People’s Hospital (Beijing, China). Methods In total, 650 patients with GD and 155 patients with AIT from December 2015 to October 2019 were included in cohort 1. Furthermore, 133 patients with GD and 14 patients with AIT from December 2019 to August 2020 were included in cohort 2 for validation of the novel index identified in cohort 1. All patients were of Chinese ethnicity and were newly diagnosed with either GD or AIT. Thyroid-related clinical information was collected before intervention by reviewing the patients’ electronic medical records. Receiver operating characteristic curve analysis was used to identify the optimal cutoff for distinguishing GD from AIT. Results In cohort 1, thyroid-stimulating hormone (TSH) receptor antibody was identified as the best indicator for distinguishing GD from AIT. The area under the receiver operating characteristic curve was 0.99(95% confidence interval: 0.98–0.99, p<0.0001)and the optimal cutoff was 0.84 IU/l (98% sensitivity and 99% specificity). The free triiodothyronine (FT3)/TSH ratio (FT3/TSH) was the second –best for distinguishing GD from AIT, the area under the receiver operating characteristic curve of FT3/TSH was 0.86 (95% confidence interval: 0.84–0.88, p<0.0001); its optimal cutoff was 1.99 pmol/mIU (79% sensitivity and 80% specificity). Its effectiveness was confirmed in cohort 2 (81% sensitivity and 100% specificity). Conclusions The FT3/TSH ratio is a new useful index for differential diagnosis of thyrotoxicosis, especially when combined with TRAb.